Normalized glandular dose coefficients in mammography, digital breast tomosynthesis and dedicated breast CT. (November 2018) - Sarno, A.; Mettivier, G.; Di Lillo, F.; Tucciariello, R.M.; Bliznakova, K.; Russo, P.
Highlights: Modeling a breast compressed in MLO view instead of in CC view does not produce any significant differences in MGD estimates. Skin model presents a noticeable influence on T-factor in DBT. Correction factor for taking into account the ion-chamber model in MGD estimates in BCT was calculated. Abstract: Purpose: To provide mean glandular dose (MGD) estimates via Monte Carlo (MC) simulations as a function of the breast models and scan parameters in mammography, digital breast tomosynthesis (DBT) and dedicated breast CT (BCT). Methods: The MC code was based on GEANT4 toolkit. The simulated compressed breast was either a cylinder with a semi-circular section or ad hoc shaped for oblique view (MLO). In DBT we studied the influence of breast models and exam parameters on the T-factors (i.e. the conversion factor for the calculation of the MGD in DBT from that for a 0-degree projection), and in BCT we investigated the influence on the MGD estimates of the ion chamber volume used for the air kerma measurements. Results: In mammography, a model representative of a breast undergoing an MLO view exam did not produce substantial differences (0.4%) in MGD estimates, when compared to a conventional cranio-caudal (CC) view breast model. The beam half value layer did not present a significant influence on T-factors in DBT (<0.8%), while the skin model presented significant influence on MGD estimates (up to 3.3% at 30 degrees scan angle), increasing for larger scan angles. We derived a correction factor for taking into account the different ion chamber volume used in MGD estimates in BCT. Conclusions: A series of MC code modules for MGD estimates in 2D and 3D breast imaging have been developed in order to take into account the most recent advances in breast models.